MiR-21 Is Required for the Epithelial-Mesenchymal Transition in MDA-MB-231 Breast Cancer Cells - RENCÜZOĞULLARI, ÖZGE; Cieza-Borrella, Clara; Miralles Arenas, Francesc; Dwek, Miriam; Lange, Sigrun; Uysal-Onganer, Pınar; ARISAN, ELİF DAMLA (MDPI, 2021)
Breast cancer (BCa) is one of the leading health problems among women. Although significant achievements have led to advanced therapeutic success with targeted therapy options, more efforts are required for different subtypes of tumors and according to genomic, transcriptomic, and proteomic alterations. This study underlines the role of microRNA-21 (miR-21) in metastatic MDA-MB-231 breast cancer cells. Following the knockout of miR-21 from MDA-MB-231 cells, which have the highest miR-21 expression levels compared to MCF-7 and SK-BR-3 BCa cells, a decrease in epithelial-mesenchymal transition (EMT) via downregulation of mesenchymal markers was observed. Wnt-11 was a critical target for miR-21, and the Wnt-11 related signaling axis was altered in the stable miR-21 knockout cells. miR-21 expression was associated with a significant increase in mesenchymal markers in MDA-MB-231 BCa cells. Furthermore, the release of extracellular vesicles (EVs) was significantly reduced in the miR-21 KO cells, alongside a significant reduction in relative miR-21 export in EV cargo, compared with control cells. We conclude that miR-21 is a leading factor involved in mesenchymal transition in MDA-MB-231 BCa. Future therapeutic strategies could focus on its role in the treatment of metastatic breast cancer.
Keywords: Breast Cancer; miR-21; Wnt-11; EMT